ANALISIS KEBERHASILAN VIKTOR AXELSEN PEMAIN DENMARK MENJADI PERINGKAT SATU DUNIA DILIHAT DARI JUMPING SMASH DAN SPEED SMASH - santoso, firman anggi (Jurnal Kesehatan Olahraga, 2019)
ABSTRACT THE SUCCESS ANALYSIS OF AXELSEN VICTOR DENISH PLAYER BECOMES A WORLD FRIST RATE SEEN FROM SMASH AND SPEED SMASH JUMPING Nama : Firman Anggi Santoso NIM : 14060484028 Program Studi : S1 ? Ilmu Keolahragaan Jurusan : Pendidikan Kesehatan dan Rekreasi Fakultas : Ilmu Keolahragaan Nama Lembaga : Universitas Negeri Surabaya Pembimbing : Dr. Himawan Wismanadi, M.Pd. Badminton is one of the most famous sport of achievement in the world. A badminton game is an individual game that can be done by one person against one or two against two. Smash blow is a form of hard blow that is often used in badminton games. The character of this punch is the hard and fast shuttlecock speeds leading to the field floor. This blow requires muscle strength of the limbs, shoulders, arms, flexibility of the wrist as well as coordination of harmonious gestures. The ability of jumping smash is considered very important role because it can generate points, when jumping smash there are some movements that need to be considered among others angle elbow, shoulder angle, jump height and smash speed. The type of this research belongs to non-experimental research type with quantitative descriptive research method, because the purpose of this research is to analyze the fact of success of Viktor Axelsen Danish national player to world number one viewed from jumping smash and speed smash in real game. Based on the observations, the percentage of the successful jumping smash done by Viktor Axelsen is 24.63% obtained from the number of jumping smashes that are successfully divided the total number of jumping smashes. From jumping smash attempt by Viktor Axelsen to get the best jumping smash 15.3386 m / s from three international badminton matches, with the angle of 138.7%, the shoulder angle of 122.4% high jump 0.23 meters. Keywords: Analysis, Badminton, Smash Jumping, Smash Speed, Angle of Elbow, Shoulder Angle